2010
DOI: 10.1128/jcm.02181-09
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Rotavirus, Adenovirus, Norovirus, and Astrovirus Infections and Coinfections among Hospitalized Children in Northern France

Abstract: stool specimens were prospectively collected from children hospitalized for gastroenteritis signs or from neonates and premature cases who were born in two French hospital settings in the north of France. They were tested by rapid enzyme immunoassay (EIA) analyses for rotavirus and adenovirus and by two commercially available ELISA tests for the detection of norovirus and astrovirus. The overall rates of prevalence for rotavirus, norovirus, adenovirus, and astrovirus were 21, 13, 5, and 1.8%, respectively, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

26
82
5
8

Year Published

2011
2011
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(122 citation statements)
references
References 19 publications
26
82
5
8
Order By: Relevance
“…This result is comparable with the results of Nimzing et al, (2000) where a prevalence of 1.1% was reported. However, our prevalence is lower than that previously reported by Aminu et al, (2008) and Tran et al, (2010) where a prevalence of 3.2% was obtained. The dual infection observed in this study may be attributable to either a single virus is responsible for the diarrhoea or the two viruses act in synergy.…”
Section: Rotavirus Adenoviruscontrasting
confidence: 54%
“…This result is comparable with the results of Nimzing et al, (2000) where a prevalence of 1.1% was reported. However, our prevalence is lower than that previously reported by Aminu et al, (2008) and Tran et al, (2010) where a prevalence of 3.2% was obtained. The dual infection observed in this study may be attributable to either a single virus is responsible for the diarrhoea or the two viruses act in synergy.…”
Section: Rotavirus Adenoviruscontrasting
confidence: 54%
“…Previous reports have demonstrated that RVA and NoV are common causes of nosocomial infections; these reports cite evidence such as aerosol transmission (especially for NoV infection) and the contamination of environmental surfaces and fomites (Wilhelmi et al 2003, Tran et al 2010). Due to the short evaluation period of this study, the seasonality of the viruses could not be inferred; however, the timing of the RVA and NoV infections (p = 0.0149) confirmed previous findings demonstrating increased positivity during the driest months (June-August) of the year in Southwest Brazil (Bittencourt et al 2000, Araújo et al 2002, Carvalho-Costa et al 2006.…”
mentioning
confidence: 99%
“…Previous reports have demonstrated that RVA and NoV are common causes of nosocomial diarrhoea in paediatric populations admitted to hospitals (Tran et al 2010). These viruses survive for extended periods under adverse environmental conditions and the morbidity of the viruses is associated with AGE infections (Bruijning-Verhagen et al 2012).…”
mentioning
confidence: 99%
“…The infections typically occur sporadically, and the cause of 2 to 10% of total viral gastroenteritis cases is attributed to HAstVs (1)(2)(3)(4)(5)(6). Astroviruses (AstVs) possess nonenveloped, icosahedrally shaped virions containing approximately 6,800 nucleotides (nt) of single-stranded positive-sense RNA (7).…”
mentioning
confidence: 99%